PENGKLASTERAN PEMERINTAH DAERAH DI JAWA DAN BALI BERDASARKAN VARIABEL SOSIOEKONOMI (KOMPARASI LAPORAN KEUANGAN DAERAH) - Baidori Baidori (ABIS: Accounting and Business Information Systems Journal, 2014)
Analysis towards financial statements of a government will be more optimal if itcompared with the similar benchmarking partners. Initiative of the localgovernment benchmarking formation has been done by Ritonga and Priyambodo(2014) through clustering model. This study aims to cluster local government inJava and Bali using K-medoids method, and then compare the clustering resultswith the study results of Priyambodo and Ritonga (2014). This study uses K-medoids method for clustering local government. Data used in this study aresocioeconomic variables contained in the allocation component of DAU. Based onthe data analysis, there were obtained five clusters of municipality and six clustersof district governments. Factor that shows a significant difference in themunicipality cluster is PDRB per capita, while in the district government cluster isthe PAD. The test results towards the criteria of cluster internal quality usingDavies-Bouldin Index (DBI) and the Silhouette index (SI) showed that theclustering results of Priyambodo dan Ritonga (2014) on municipal government isbetter than the results of this study, whereas the result of district governmentclustering in this study is better than the study results of Priyambodo and Ritonga(2014).